2017
DOI: 10.1021/acsami.6b13986
|View full text |Cite
|
Sign up to set email alerts
|

Segregated Hybrid Poly(methyl methacrylate)/Graphene/Magnetite Nanocomposites for Electromagnetic Interference Shielding

Abstract: Nanocomposites of poly(methyl methacrylate)/reduced graphene oxide (PMMA/rGO) without and with decorated magnetite nanoparticles with a segregated structure were prepared using emulsifier-free emulsion polymerization. Various characterization techniques were employed to validate the presence of the nanofillers and the formation of the segregated structure within the nanocomposites. The percolation threshold of the nanocomposites was found to be 0.3 vol %, while a maximum electrical conductivity of 91.2 S·m and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
155
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 316 publications
(163 citation statements)
references
References 68 publications
6
155
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11] In addition, EM radiation is a major concern for human health without other metallic-or nonmetallic-particles [40,42,51,53,[55][56][57][58][59][60] as fillers in various composites for EMI shielding purposes. As the electronic devices decrease in size, and operate at ever increasing frequencies, they produce more heat and EM waves, which result in faster degradation of such devices and negative effects on adjacent electronic systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10][11] In addition, EM radiation is a major concern for human health without other metallic-or nonmetallic-particles [40,42,51,53,[55][56][57][58][59][60] as fillers in various composites for EMI shielding purposes. As the electronic devices decrease in size, and operate at ever increasing frequencies, they produce more heat and EM waves, which result in faster degradation of such devices and negative effects on adjacent electronic systems.…”
Section: Introductionmentioning
confidence: 99%
“…The heat and EM radiation have an inherent connection-absorption of EM waves by any material results in its heating. Several studies reported the use of carbon fibers, [22][23][24][25][26][27][28][29] carbon black, [30,31] bulk graphite, [32][33][34] carbon nanotubes (CNT), [16,17,[35][36][37][38][39] reduced graphene oxide (rGO), [2,6,[40][41][42][43][44][45][46][47][48][49][50] graphene, [51][52][53][54] and combination of carbon allotropes with orThe synthesis and characterization of epoxy-based composites with few-layer graphene fillers, which are capable of dual-functional applications, are reported. The conventional approach for handling the heat and EM radiation problems is based on utilization of the thermal interface materials (TIM), which can spread the heat, and electromagnetic interference (EMI) shielding materials, which can protect from EM waves.…”
mentioning
confidence: 99%
“…The PASS/GNPs phase is used to construct 3D continuous conductive networks, meaning that the networks could be treated as “conductive network cages.” The cages own many interfaces and the electromagnetic wave that are captured in the cages can be attenuated by multiple reflection and absorption. Finally, the great part of electromagnetic energy can be dissipated in the form of heat …”
Section: Resultsmentioning
confidence: 99%
“…used the compression‐molded method to prepare carbon nanotube (CNT)/ground tire rubber composites with a segregated structure, demonstrating an electrical conductivity of 2.6 S m −1 and an EMI SE of 24.5 dB with only 1.0 wt % CNT loading . The segregated reduced graphene oxide (rGO)/poly(methyl methacrylate) (PMMA) composites were fabricated using emulsifier‐free emulsion polymerization, which exhibited an EMI SE of 20.7 dB with 1.1 vol % rGO content . Other CPCs also showed the similar results, involving rGO/poly(vinylidene fluoride), graphene/polycarbonate (PC), CNT/polylactic acid (PLA), and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…Two main mechanisms are involved in EMI shielding, viz. reflection and absorption . When an EM wave hits a conductive shield, a portion of the EM wave is reflected off the shield owing to interaction with the surface free charge carriers, and a fraction penetrates through the shield with its energy dissipated via absorption.…”
Section: Resultsmentioning
confidence: 99%